A comparative study on the cesium retention ability up to 1750 °C in Cs–Zr–Si–O, Cs–Al–Si–O, and Cs–Si–O. Issue 12 (15th August 2019) - Jeon, Sang-Chae; Kim, Dong-Joo; Kim, Dong Seok; Kim, Keon Sik; Kim, Jong Hun; Yoon, Ji Hae; Yang, Jae Ho
Abstract: As cesium-trapping agents in an accident-tolerant fuel (ATF) that reduces fission gas release (FGR), Al–Si–O and Zr–Si–O (resulting in Cs–Al–Si–O and Cs–Zr–Si–O) are considered promising due to their good cesium retention ability up to high temperatures. However, in previous research, there is a lack of experimental data to compare them and determine which material is superior. In this study, the cesium retention ability of these materials was assessed by observing their weight loss behaviors up to 1750 °C. Other cesium compounds, such as pollucite (CsAlSi2 O6 ) and Cs–Si–O possibly formed in the real fuel environment were also compared. As a result, Cs–Al–Si–O (CsAlSiO4 ) exhibited the most favorable result. It released cesium at higher temperatures and showed lower loss rate: only 2.36% of captured cesium was released at 1750 °C when sufficiently homogenized at 1050 °C. The real nuclear fuel environment in the light water reactor (LWR) was taken into account for the interpretation of comparative results, demonstrating that Al–Si–O is the most advantageous trapping agent in terms of high-temperature cesium retention ability.